2014
DOI: 10.1080/14615517.2014.898386
|View full text |Cite
|
Sign up to set email alerts
|

Is environmental impact assessment fulfilling its potential? The case of climate change in renewable energy projects

Abstract: One of the topics receiving much attention in recent years is climate change and the potential of its integration in impact assessment, both in terms of achieving mitigation and adaptation. Renewable energy projects are part of the efforts to mitigate climate change, replacing the use of fossil fuel with CO 2 -neutral energy sources. A variety of these projects are subject to environmental impact assessment (EIA), which raises the following questions: What role does an impact assessment play? When is the proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Through the last decade, there has been discussion, analysis, and guidance published on whether and how the challenge of climate change should be handled in impact assessment (see e.g. Agrawala et al 2012;Wilson 2010;Larsen 2014;McGuin et al 2013a andMcGuin et al 2013b). It has been suggested that climate change should be integrated into impact assessment through three approaches (Larsen and Kørnøv 2009):…”
Section: Challenges In Practice: Climate Change In Strategic Environmmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the last decade, there has been discussion, analysis, and guidance published on whether and how the challenge of climate change should be handled in impact assessment (see e.g. Agrawala et al 2012;Wilson 2010;Larsen 2014;McGuin et al 2013a andMcGuin et al 2013b). It has been suggested that climate change should be integrated into impact assessment through three approaches (Larsen and Kørnøv 2009):…”
Section: Challenges In Practice: Climate Change In Strategic Environmmentioning
confidence: 99%
“…Internationally, a study prepared for the European Commission points out that in SEA 'specific attention to climate change issues appears still to be limited in many Member States' (COWI 2009, 116). In EIA, a study published by Larsen (2014) indicates a larger emphasis on integration of climate change. Here, 18 out of 19 studied EIA statements integrated climate change, although, as was the case for SEA, the primary focus is on mitigation, since none of the statements mention climate change adaptation or baseline adaptation (Larsen 2014).…”
Section: Challenges In Practice: Climate Change In Strategic Environmmentioning
confidence: 99%
See 1 more Smart Citation
“…A major aim of the research project was to overcome the science-policy-practice-divide [26][27][28] in mainstreaming climate change into EIA. The mixed-methods approach and in particular the backcasting scenario building process helped to tackle barriers -such as lack of data, specifications, guidance and legal frameworks as well as capacity and awareness of actors -identified previously by earlier studies [29][30][31][32] and allow actors with different knowledge of climate change impacts and their relevance for impact assessment to participate actively in the discourses. This paper discusses both the transdisciplinary process -focusing on the backcasting approach in scenario analysis -and the interdisciplinary findings for EIA and SEA practice.…”
Section: Introductionmentioning
confidence: 99%
“…EIA is nowadays considered a modern tool of developed societies for the achievement of appropriate compromises between development and environment, aiming at the inclusion of environmental concerns in decision-making and ultimately at promoting a more sustainable development [42,43]. An EIA enables the assessment of the environmental impacts of a project occurring during the planning phase of its life cycle, and includes impact assessment, as well as mitigation and prevention measures throughout the whole project's life cycle.…”
Section: Introductionmentioning
confidence: 99%